2019
DOI: 10.1101/537431
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Blood-brain barrier dysfunction in aging induces hyper-activation of TGF-beta signaling and chronic yet reversible neural dysfunction

Abstract: Aging involves a decline in neural function that contributes to cognitive impairment and disease. However, the mechanisms underlying the transition from a young-and-healthy to aged-anddysfunctional brain are not well understood. Here, we report breakdown of the vascular blood-brain barrier (BBB) in aging humans and rodents, which begins as early as middle age and progresses to the end of the lifespan. Gain-of-function and loss-of-function manipulations show that this BBB dysfunction triggers hyperactivation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(35 citation statements)
references
References 100 publications
(126 reference statements)
0
34
0
Order By: Relevance
“…Pharmacological inhibition of TGF‐ β signaling reversed these symptomatic outcomes in aged mice. [ 217 ] Several lines of evidence from animal studies also support a role for IL‐1 β in BBB dysfunction during neuroinflammation. Treatment of IL‐1 β receptor antagonists or genetic deletion of the IL‐1 receptor attenuates BBB hyperpermeability induced by neuroinflammation in mice.…”
Section: Neuroinflammation and The Bbbmentioning
confidence: 99%
See 1 more Smart Citation
“…Pharmacological inhibition of TGF‐ β signaling reversed these symptomatic outcomes in aged mice. [ 217 ] Several lines of evidence from animal studies also support a role for IL‐1 β in BBB dysfunction during neuroinflammation. Treatment of IL‐1 β receptor antagonists or genetic deletion of the IL‐1 receptor attenuates BBB hyperpermeability induced by neuroinflammation in mice.…”
Section: Neuroinflammation and The Bbbmentioning
confidence: 99%
“…When inflammation is present, an altered BBB breaks the immune privilege of the brain, exposing neuronal antigens to the peripheral inflammatory molecules, which further stimulate the inflammatory response in the brain, leading to accelerated neurological disease development. [216][217][218][219] As such, communication between the immune system and the brain has become recognized as a central element of healthy brain function. [220] On one hand, targeting inflammation restores BBB integrity, which in turn benefits the treatment of neurological diseases associated with neuroinflammation.…”
Section: Virus-based Deliverymentioning
confidence: 99%
“…The CSF-to-plasma albumin ratio has usually been used to follow the increase in BBB permeability during aging [106]. A dynamic contrast-enhanced MRI study of 113 cognitively normal subjects aged 21-83 years by Senatorov et al [107] found that the increase begins in mid-life, and Chen et al [108] have calculated that, in comparison with young barriers that can stop proteins with a molecular weight of >91.9 kDa, elderly barriers can be crossed by heavier molecules of up to 120 kDa. Some capillaries are more vulnerable to permeability failure than others, thus suggesting where BBB dysfunction may start.…”
Section: Blood-brain Barriermentioning
confidence: 99%
“…In addition, a senescent BBB may interfere with their ability to cross vessel walls, which normally occurs at venule level. Conversely, increased BBB permeability allows plasma albumin to enter astrocytes and overactivate neurotoxic cytokines [107], particularly in patients whose peripheral inflammation is responsible for further endothelial and perivascular cell involvement [154]. Perry and Holmes [155] have underlined the role of β-protein and misfolded proteins in microglial priming, whereas Safaiyan et al [156] have observed microglia that become senescent after accumulating membrane debris from myelin turnover.…”
Section: Microglia and Macrophagesmentioning
confidence: 99%
“…One potential physiological trigger of astrocyte senescence is age-associated BBBD and subsequent TGFβ signaling activation. BBBD enables blood-borne proteins such as serum albumin (Bar-Klein et al, 2014; Cacheaux et al, 2009; Senatorov et al, 2019; Weissberg et al, 2015) and fibrinogen (Schachtrup et al, 2010) to extravasate into the brain parenchyma, where they elicit a robust inflammatory response by activating canonical TGFβ signaling. In astrocytes, albumin binds to the type II TGFβR, which dimerizes and subsequently activates the type I TGFβR ALK5 before undergoing receptor-mediated endocytosis.…”
Section: Introductionmentioning
confidence: 99%